1996
DOI: 10.1017/s0714980800013271
|View full text |Cite
|
Sign up to set email alerts
|

The Free Radical Theory of Aging and a Look at Changes in the Hypothalamus

Abstract: RÉSUMÉSelon la théorie du radical libre, le vieillissement est produit par l'effet endommageant des radicaux d'oxygène. Ces radicaux sont produits de façon constante et deviennent toxiques quand le niveau de la concentration intracellulaire devient élevé. Malgré cet effet d'infamie, des études récentes indiquent qu'ils peuvent avoir un côté bénéfique en régulant certains mécanismes dans une cellule. Mais, avec le vieillissement, il semble que la capacité de réguler la concentration intracellulaire s'abaisse, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…There is an increase in adrenal glucocorticoid secretion, as well as a decline in adrenal androgen synthesis and secretion in humans during the aging process (Yen and Laughlin, 1998). Several investigators have suggested that the hypothalamus may mediate the agerelated decline of physiological functions and changes of biological rhythms (Meites et al, 1987;Carlson and Sawada, 1996;Hofman, 1997); the hippocampus has also been implicated in this phenomenon (Jacobson and Sapolsky, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increase in adrenal glucocorticoid secretion, as well as a decline in adrenal androgen synthesis and secretion in humans during the aging process (Yen and Laughlin, 1998). Several investigators have suggested that the hypothalamus may mediate the agerelated decline of physiological functions and changes of biological rhythms (Meites et al, 1987;Carlson and Sawada, 1996;Hofman, 1997); the hippocampus has also been implicated in this phenomenon (Jacobson and Sapolsky, 1991).…”
Section: Introductionmentioning
confidence: 99%